Digitization of SISKEUDES and Village Government Governance: The Role of Competency Moderation of Village Apparatus - D. Dewila (Golden Ratio of Data in Summary, 2026)
This study aims to examine the influence of the digitalization of the Village Financial System (SISKEUDES) on the governance of village governments in Mamuju Regency, considering the moderating roles of village apparatus competence, fraud prevention, and the effectiveness of village financial management. A quantitative approach was employed, with data collected through surveys of 150 village officials. The data were analyzed using multiple linear regression and interaction effect tests. The results reveal that SISKEUDES digitalization has a significant positive impact on village governance. Financial management effectiveness also shows a significant influence, while fraud prevention and apparatus competence do not have direct effects. However, the interaction analysis indicates that village apparatus competence strengthens the influence of fraud prevention on governance but unexpectedly weakens the relationship between financial management effectiveness and governance. Meanwhile, competence does not moderate the effect of digitalization on governance. These findings underscore the importance of integrating digital financial systems with institutional factors such as human resource competence and internal control. The success of SISKEUDES implementation is not solely determined by technological capacity but also relies heavily on the quality of personnel and governance infrastructure to achieve transparency, accountability, and public participation in local government.